An innovative method of pilot balloon capping for submental intubation - Kiran, Molli; Padala, Sri Rama Ananta Nagabhushanam; Preeti, Preeti; Seema, Seema; Kuttan, Koovakattil Akhil (Journal of dental anesthesia and pain medicine: JDAPM, 2024)
KCI Citation Count: 0